Comparison of continuous wave and cold lateral condensation filling techniques in 3D printed simulated C-shape canals instrumented with Reciproc Blue or Hyflex EDM - GENÇOĞLU, NİMET (PUBLIC LIBRARY SCIENCE, 2019)
Aim To compare the efficiency of continuous wave obturation and cold lateral condensation techniques and filling time in C-shape canals of 3-dimensional (3D)-printed resin teeth shaped with Reciproc Blue (VDW) or Hyflex EDM (Coltene/Whaledent). Methodology One tooth with C1-type orifice and root canal morphology and one with C2-type orifice and C2-C3 root canal morphology were selected based on CBCT. Two replicas of selected teeth were manufactured with a 3D-printer and their canals were instrumented with Reciproc Blue or Hyflex EDM. These 4 instrumented replicas were scanned with CBCT. Identical 10 replicas of each group (total of 40) were produced using a 3D-printer and randomly divided into 2 groups (n = 5), root filled with either continuous wave obturation (CW) or cold lateral condensation (LC). Horizontal cross-sections of C1-type were made at 2, 4, 6, 8 mm and C2-type at 2, 4, 6 mm from the apical foramen. Gutta-percha, sealer and void areas were evaluated with image analysis sofware. Data were analysed using nonparametric Kruskal-Wallis and Mann Whitney-U tests and the Factorial ANOVA was used for interaction effects. Time required to fill canals was evaluated using the Mann-Whitney U test. Results For C1-type, LC had more gutta-percha and less sealer compared to CW in 2-mm sections (p<0.05). CW had greater percentages of gutta-percha and lower percentages of sealer compared with LC group in 4, 6, 8 mm sections and total area (p<0.05). LC group had higher percentages of voids compared to CW group in 2 and 4 mm sections (p<0.05). For C2-type, CW had more gutta-percha and less sealer versus LC group in all sections and total area (p<0.05). LC had the least gutta-percha and greatest sealer percentages at 6-mm sections (p<0.05). There was no statistically significant difference in the percentages of voids at any level of sections between the filling techniques (p>0.05). In both C-types, there was no significant difference in the percentages of gutta-percha, sealer and voids between Reciproc Blue and Hyflex EDM-shaped groups at any level (p>0.05). Time spent for the LC technique and filling C1-type was significantly longer than when using the CW technique and filling C2-type (p<0.05). Conclusions Continuous wave obturation was more effective than lateral condensation in both C1- and C2-type, except for the apical 2 mm section of C1-type, suggesting the need for a modified CW technique.
Keywords: MANDIBULAR 2ND MOLARS; ROOT CANALS; PART II; 1ST MOLAR; SYSTEM; CONFIGURATION; POPULATION; OBTURATIONS; 2ND-MOLARS; MICROSEAL